IDENTIFICATION OF SOME STRAINS OF DINOFLAGELLATES BASED ON MORPHOLOGY AND MOLECULAR ANALYSIS (Makara Journal of Science, 2008)
Dinoflagellates are the important primary producers in aquatic environments. In oceans, they play interesting role in ecological functions such as red tide forming organisms, symbiont of coral reef or sea anemone and DSP (Diarrhetic Shellfish Poisoning) or PSP (Paralytic Shellfish Poisoning) producing organisms. Morphology and molecular analysis of dinoflagellates were conducted on November 2002 to March 2003. The phylogenetic studies based on 18S rDNA analyses, sequence have begun to appear more frequently in the literature, as attention has turned to relationships within the major eukaryotic lineages, particular importance for the taxonomy of the armored and unarmored genera of dinoflagellates (Gyrodinium sp., Cachonina sp., Gymnodinium sp., Amphidinium sp.), because many of the genera cause extensive plankton blooms, fish kills and other harmful events, were studied used to amplify 18S rDNA, present in the total DNA extracted from algal pellet. The amplify approximately 1400 bp of the nuclear-encoded LSU rDNA gene using terminal primeirs DIR, products were cheked by 1.0 % agarose gel electrophoresis, then cloning with TA cloning KIT. Sequencing were analyzed by the GENETIX Mac Software, Homology search by Blast and Phylogenetic analysis. Results of hylogenetic analysis of 18S rDNA are: Strain no. 10893 (un identified) from the genera, it is belonging Gymnodinium or Polarella. Strain no. 10795 is closely related other species Cachonina hallii. We tentatively named strain no 11151 and 11160 similar to Gyrodinium or Gymnodinium based on morphology, but these strain indepently position in this tree and is not a real of Gymnodinium sensu stricto. It is possible, we can establish the new genera for strain no. 11151; 11160 because this not cluster any other unarmored species.